2010
DOI: 10.1111/j.1365-2893.2010.01271.x
|View full text |Cite
|
Sign up to set email alerts
|

Virological, serological and biochemical outcomes through 3 years of entecavir treatment in nucleoside‐naive Chinese chronic hepatitis B patients

Abstract: SUMMARY. Hepatitis B virus (HBV) infection has a high prevalence in China. Entecavir has shown superior efficacy over lamivudine in Chinese nucleoside-naive chronic hepatitis B (CHB) patients over 48 weeks, with continued clinical benefit to 96 weeks. The present study evaluates the long-term efficacy of entecavir in Chinese CHB patients who continued entecavir treatment for 144 weeks. Patients receiving either entecavir 0.5 mg/day (n = 258) or lamivudine 100 mg/day (n = 261) entered the initial 96-week random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 20 publications
6
17
1
Order By: Relevance
“…In our large multicentred cohort consisting almost entirely of Asian adults, we found that antiviral treatment (ETV or TDF in 94% of patients) over a median duration of almost six and one‐half years resulted in a 4.58% overall rate of HBsAg loss, 4.44% in HBeAg‐positive patients and 4.71% in HBeAg‐negative patients. The loss in HBeAg‐negative patients is striking in comparison with multiple previous studies in which HBsAg loss with antiviral therapy has ranged from 0% to 0.7% in HBeAg‐negative patients treated with ETV, TDF or TDF/FTC . It is not clear why significantly higher rates of HBsAg loss were seen among our cohort of HBeAg‐negative patients.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…In our large multicentred cohort consisting almost entirely of Asian adults, we found that antiviral treatment (ETV or TDF in 94% of patients) over a median duration of almost six and one‐half years resulted in a 4.58% overall rate of HBsAg loss, 4.44% in HBeAg‐positive patients and 4.71% in HBeAg‐negative patients. The loss in HBeAg‐negative patients is striking in comparison with multiple previous studies in which HBsAg loss with antiviral therapy has ranged from 0% to 0.7% in HBeAg‐negative patients treated with ETV, TDF or TDF/FTC . It is not clear why significantly higher rates of HBsAg loss were seen among our cohort of HBeAg‐negative patients.…”
Section: Discussioncontrasting
confidence: 64%
“…Two studies have shown no sAg loss in NUC‐treated Asian patients after 3‐5 years of therapy. In 160 Chinese patients who received continuous entecavir (ETV) therapy for 3 years, there was no HBsAg loss in either HBeAg‐positive or HBeAg‐negative patients . In a subgroup analysis of 94 HBeAg‐positive Asian patients included in the overall long‐term ETV cohort, it was shown that with 5 years of ETV therapy there was still no HBsAg loss …”
Section: Introductionmentioning
confidence: 99%
“…Overall, these results demonstrate superior antiviral efficacy of entecavir compared with lamivudine, adefovir, and telbivudine, and support the current Asian-Pacific treatment guidelines recommendation to use entecavir as a first-line therapeutic option for patients with CHB. In addition, a number of studies in the People’s Republic of China have directly compared entecavir with other nucleos(t)ide analogs that are currently recommended, including lamivudine, adefovir, and telbivudine 2129…”
Section: Efficacy Of Entecavir Compared With Other Hbv Treatment Optionsmentioning
confidence: 99%
“…Entecavir has demonstrated efficacy superior to that of lamivudine in a number of studies comparing the two therapies in Chinese patients with CHB 2124. A multicenter study evaluated the long-term efficacy of entecavir in patients who continued entecavir therapy for up to 144 weeks 21.…”
Section: Entecavir Versus Lamivudinementioning
confidence: 99%
See 1 more Smart Citation